Carbon composite transition metal fluoride positive electrode material and preparation method and application thereof

By heat-treating the transition metal element under vacuum conditions and gas-phase reaction with the fluorine source gas on the porous carbon substrate, carbon composite transition metal fluoride nanoparticles are generated, which solves the problems of low capacity and poor cycle stability of traditional positive electrode materials, and achieves high capacity and excellent electrochemical performance.

CN119812231AActive Publication Date: 2025-04-11LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311309419.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

The low specific capacity of traditional intercalation electrode materials cannot meet the needs of high-capacity positive electrode materials. The poor electronic conductivity and structural collapse of transition metal fluoride lead to poor battery capacity attenuation and cycle stability.

Method used

By heat-treating the transition metal element under vacuum, it is gasified, and then reacting with the fluorine source gas on the porous carbon substrate to generate carbon composite transition metal fluoride nanoparticles, improving its electronic conductivity and cycling performance.

Benefits of technology

The electronic conductivity and cyclic performance of carbon composite transition metal fluoride cathode material is improved, and the problems of low reversible capacity and fast capacity decay are overcome, and excellent rate performance and cyclic performance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812231A_ABST
    Figure CN119812231A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a carbon composite transition metal fluoride positive electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: under a vacuum condition, carrying out heat treatment on a transition metal simple substance, so that the transition metal simple substance is gasified into gaseous metal nanoparticles, and transition metal steam is obtained; transition metal steam and fluorine source gas are introduced into the reaction container containing the porous carbon substrate, the transition metal steam and the fluorine source gas are subjected to a gas-phase reaction, transition metal fluoride nanoparticles are generated and deposited on the surface of the porous carbon substrate in situ, and the carbon composite transition metal fluoride positive electrode material is obtained. The carbon composite transition metal fluoride positive electrode material prepared by the preparation method provided by the invention has relatively good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary battery positive electrode materials, and in particular to a carbon composite transition metal fluoride positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high energy conversion efficiency and long service life, and are widely used in portable mobile devices, electric vehicles, etc. However, the low specific capacity of traditional intercalation electrode materials cannot meet people's urgent demand for high-capacity positive electrode materials.

[0003] Transition metal fluorides are considered to have great application prospects in the next generation of cathode materials due to their high operating voltage and capacity, low cost, wide source, good thermal stability, and environmental friendliness. 3 ) due to its high 712mAh g -1 Transition metal fluorides have been widely studied due to their theoretical capacity and working potential greater than 3.0V. However, the large energy band width of transition metal fluorides leads to poor electronic conductivity, which greatly limits the storage capacity of lithium. In addition, the structural collapse caused by the conversion reaction can easily cause problems such as battery capacity decay and poor cycle stability, which restricts the commercial development of transition metal fluorides.

[0004] In order to overcome the above problems, researchers have tried to prepare carbon composite transition metal fluorides using solvothermal method, precipitation method and ball milling method, but these methods all have certain shortcomings. For example, the composite material prepared by ball milling has large particle size, low tap density, small specific surface area and poor electrochemical performance; the solvothermal method takes a long time, the prepared particles are large, and are often accompanied by crystal water that is difficult to remove, and often have poor cycle performance. In short, the electrode materials obtained by the above methods need to be improved in terms of reversible specific capacity, rate performance and cycle performance. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon composite transition metal fluoride positive electrode material and its preparation method and application in view of the defects of the prior art. The carbon composite transition metal fluoride positive electrode material prepared by the preparation method overcomes the problems of low reversible capacity and fast capacity decay of the transition metal fluoride positive electrode material, and improves the electrochemical performance.

[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a carbon composite transition metal fluoride positive electrode material, the preparation method comprising:

[0007] Under vacuum conditions, heat-treating a transition metal element so that the transition metal element is vaporized into gaseous metal nanoparticles to obtain transition metal vapor;

[0008] The transition metal vapor and the fluorine source gas are introduced into a reaction container containing a porous carbon substrate, and the transition metal vapor and the fluorine source gas undergo a gas phase reaction to generate transition metal fluoride nanoparticles, which are in situ deposited on the surface of the porous carbon substrate to obtain a carbon composite transition metal fluoride positive electrode material.

[0009] Preferably, the vacuum condition is: the vacuum degree is less than 10 -3 pa; the heat treatment temperature is 300°C-3000°C, and the different transition metal elements correspond to different heat treatment temperatures.

[0010] Preferably, the heat treatment includes any one of resistance heating, high frequency induction heating, laser heating, electron beam heating, microwave heating or arc heating.

[0011] Preferably, the gas flow rates of the transition metal vapor and the fluorine source gas are both 10 ml / min-30 ml / min; and the reaction time of the gas phase reaction is 0.5 hour-6 hours.

[0012] Preferably, the molar ratio of the metal element in the transition metal vapor to the fluorine element in the fluorine source gas is 1:1-1:6.

[0013] Preferably, the transition metal single substance includes any one of the metal elements Fe, Co, Mn, Ni, Cu, Zn, Nb or Ti; and the purity of the transition metal single substance is greater than 99.8%.

[0014] Preferably, the fluorine source gas is nitrogen trifluoride or carbon tetrafluoride.

[0015] In a second aspect, the present invention provides a carbon composite transition metal fluoride positive electrode material, wherein the carbon composite transition metal fluoride positive electrode material is prepared by any preparation method described in the first aspect above.

[0016] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the carbon composite transition metal fluoride positive electrode material described in the second aspect above.

[0017] In a fourth aspect, the present invention provides a secondary battery, characterized in that the secondary battery comprises the positive electrode sheet described in the third aspect.

[0018] The preparation method of the carbon composite transition metal fluoride positive electrode material provided in the embodiment of the present invention is to gasify the transition metal element by heat treatment, then react with the fluorine source gas in gas phase, and then deposit it on a porous carbon substrate, thereby obtaining a carbon composite transition metal fluoride positive electrode material; the carbon composite transition metal fluoride positive electrode material has the advantage of high specific capacity of transition metal fluoride, and constructs an electron transmission conductive network between nanoparticles by in-situ composite of transition metal fluoride and carbon, which significantly improves the electronic conductivity of the carbon composite transition metal fluoride positive electrode material. The porous carbon substrate can provide an effective buffer space for the volume expansion and contraction of the carbon composite transition metal fluoride positive electrode material, so that it has excellent cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A flow chart of a method for preparing a carbon composite transition metal fluoride positive electrode material provided in an embodiment of the present invention;

[0020] Figure 2 This is a charge and discharge curve diagram of the carbon composite iron fluoride positive electrode material prepared in Example 1 of the present invention;

[0021] Figure 3 This is a cycle performance diagram of the carbon composite iron fluoride positive electrode material prepared in Example 1 of the present invention;

[0022] Figure 4 This is a charge and discharge curve diagram of the carbon composite copper fluoride positive electrode material prepared in Example 2 of the present invention;

[0023] Figure 5 This is a cycle performance diagram of the carbon composite copper fluoride positive electrode material prepared in Example 2 of the present invention;

[0024] Figure 6 This is a charge and discharge curve diagram of the carbon composite cobalt fluoride positive electrode material prepared in Example 3 of the present invention;

[0025] Figure 7 This is a cycle performance diagram of the carbon composite cobalt fluoride positive electrode material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a method for preparing a carbon composite transition metal fluoride positive electrode material, the process of which is as follows: Figure 1 As shown, the following steps are included:

[0028] Step 110, heat-treating the transition metal element under vacuum conditions to vaporize the transition metal element into gaseous metal nanoparticles to obtain transition metal vapor;

[0029] This step is mainly to gasify the transition metal element. The vacuum degree of the vacuum condition is less than 10 -3 pa. The heat treatment method may specifically include any one of resistance heating, high frequency induction heating, laser heating, electron beam heating, microwave heating or arc heating. The heat treatment temperature may specifically be 300°C-3000°C, and different transition metal elements correspond to different heat treatment temperatures. The transition metal element may specifically include any one of the metal elements Fe, Co, Mn, Ni, Cu, Zn, Nb or Ti. The purity of the transition metal element is greater than 99.8%.

[0030] Step 120, introducing transition metal vapor and fluorine source gas into a reaction container containing a porous carbon substrate, the transition metal vapor and the fluorine source gas undergo a gas phase reaction to generate transition metal fluoride nanoparticles, which are in situ deposited on the surface of the porous carbon substrate to obtain a carbon composite transition metal fluoride positive electrode material.

[0031] Specifically, the fluorine source gas can be nitrogen trifluoride or carbon tetrafluoride. The molar ratio of the metal element of the transition metal vapor and the fluorine of the fluorine source gas is 1:1-1:6. The gas flow rate when the transition metal vapor and the fluorine source gas are introduced can be 10 ml / min-30 ml / min. The reaction time of the gas phase reaction is 0.5 hours-6 hours. The porous carbon substrate can be any one of carbon fiber, carbon nanorod, carbon nanowire, carbon nanostick, single-walled carbon nanotube, multi-walled carbon nanotube, graphite, graphene, carbon cloth, carbon paper, biomass-derived carbon, metal organic framework (Metal Organic Framework, MOF) / polymer-derived porous carbon. The transition metal fluoride generated by the gas phase reaction can specifically include FeF 2 , FeF 3 , CoF 2 , CoF 3 、MnF 2 、MnF 3 、NiF 2 、NiF 3 ,CuF 2 、ZnF 2 ,NbF 5 、TiF 4 Any of .

[0032] The atomic-level mixing is achieved through the gas phase reaction between transition metal vapor and fluorine source gas, with a short reaction time and more complete reaction. The carbon of the porous carbon substrate surrounding the gaseous metal nanoparticles plays the role of a microreactor during the reaction, limiting the agglomeration of transition metal fluoride particles, making the resulting transition metal fluoride particles smaller, with a large specific surface area and controllable morphology.

[0033] The carbon in-situ composite of transition metal fluoride particles and porous carbon substrate constructs an electron transport conductive network between nanoparticles, which can improve the electronic conductivity of the material. During the lithium ion deintercalation process, the porous carbon substrate can provide an effective buffer space for the volume expansion and contraction of the positive electrode material, thereby exhibiting excellent cyclability and rate performance, overcoming the problems of low reversible capacity and rapid capacity decay of transition metal fluoride positive electrode materials, and improving the electrochemical performance.

[0034] The preparation method of the carbon composite transition metal fluoride positive electrode material provided in the embodiment of the present invention is to gasify the transition metal element by heat treatment, then react with the fluorine source gas in gas phase, and then deposit it on a porous carbon substrate, thereby obtaining a carbon composite transition metal fluoride positive electrode material; the carbon composite transition metal fluoride positive electrode material has the advantage of high specific capacity of transition metal fluoride, and constructs an electron transmission conductive network between nanoparticles by in-situ composite of transition metal fluoride and carbon, which significantly improves the electronic conductivity of the carbon composite transition metal fluoride positive electrode material. The porous carbon substrate can provide an effective buffer space for the volume expansion and contraction of the carbon composite transition metal fluoride positive electrode material, so that it has excellent cycle performance and rate performance.

[0035] The carbon composite transition metal fluoride positive electrode material provided by the present invention can be applied to the positive electrode material of secondary batteries. By using the carbon composite transition metal fluoride as the positive electrode material of lithium-ion batteries, the dependence on lithium resources is reduced, and the shortage and high price of elements such as nickel and cobalt in the positive electrode materials of lithium-ion batteries are solved.

[0036] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the specific process of preparing a carbon composite transition metal fluoride positive electrode material using the method provided in the above embodiment of the present invention, as well as the electrochemical properties of the prepared carbon composite transition metal fluoride positive electrode material.

[0037] Example 1

[0038] In the first step, the vacuum degree is 4×10 -4 Under the condition of pa, metallic iron with a purity of 99.9% is placed in a resistance heater and heated to 1300°C by resistance, so that the metallic iron is vaporized into gaseous iron nanoparticles to obtain iron vapor, which is then collected.

[0039] In the second step, iron vapor and nitrogen trifluoride gas are introduced into the reactor at a molar ratio of iron to fluorine of 1:3 and an air flow rate of 10 ml / min. The reaction time is 2 hours to generate iron fluoride nanoparticles, which are in situ deposited on the surface of the carbon fiber substrate to obtain a carbon composite iron fluoride positive electrode material, which is then collected after cooling.

[0040] The obtained carbon composite iron fluoride positive electrode material, conductive agent acetylene black and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, stirred until the viscosity reached the coating requirement, and then the mixture was evenly applied on aluminum foil using a coating machine. It was vacuum dried at 80°C for 12 hours.

[0041] After that, the dried electrode was cut into discs with a diameter of 12 mm, and the loading amount of active material on each disc was 2 mg / cm 2 .

[0042] The prepared electrode sheet was used as the positive electrode, the lithium sheet as the negative electrode, and Celgard 2500 as the separator. The entire process was completed in an argon-filled glove box to complete the assembly of the CR2032 button battery. The electrolyte of the assembled CR2032 button battery was 1 mol / L lithium hexafluorophosphate (LiPF 6 ), the solvent of the electrolyte is ethylene carbonate (EC) and dimethyl carbonate (DMC), wherein the volume ratio of EC to DMC is 1:1.

[0043] After assembly, the button cell was left to stand for 8 hours. At room temperature, the charge, discharge and cycle tests were performed on a Blue Power Battery Test System (CT2001A) with a test voltage of 2.2-4.2V and a current density of 0.1C to evaluate its electrochemical performance.

[0044] Example 2

[0045] In the first step, the vacuum degree is 1×10 -4 Under the condition of pa, metallic copper with a purity of 99.95% is placed in an inductor made of a hollow metal tube and heated to 1100°C by high-frequency induction, so that the metallic copper is vaporized into gaseous copper nanoparticles to obtain copper vapor, which is then collected.

[0046] In the second step, copper vapor and carbon tetrafluoride gas are introduced into the reactor at a molar ratio of copper element to fluorine element of 1:2 and a gas flow rate of 15 ml / min. The reaction time is 3 hours to generate copper fluoride nanoparticles, which are in situ deposited on the surface of the multi-walled carbon nanotube substrate to obtain a carbon composite copper fluoride positive electrode material, which is then collected after cooling.

[0047] The obtained carbon composite copper fluoride positive electrode material, conductive agent acetylene black and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, stirred until the viscosity reached the coating requirement, and then the mixture was evenly applied on aluminum foil using a coating machine. It was vacuum dried at 80°C for 12 hours.

[0048] After that, the dried electrode was cut into discs with a diameter of 12 mm, and the loading amount of active material on each disc was 3 mg / cm 2 .

[0049] The prepared electrode sheet was used as the positive electrode, the lithium sheet as the negative electrode, and Celgard 2500 as the separator. The entire process was completed in an argon-filled glove box to complete the assembly of the CR2032 button battery. The electrolyte of the assembled CR2032 button battery was 1 mol / L lithium hexafluorophosphate (LiPF 6 ), the solvent of the electrolyte is ethylene carbonate (EC) and dimethyl carbonate (DMC), wherein the volume ratio of EC to DMC is 1:1.

[0050] After assembly, the button cell was left to stand for 8 hours. At room temperature, the charge, discharge and cycle tests were performed on a Blue Power battery test system (CT2001A) with a test voltage of 1.5-4.4V and a current density of 0.1C to evaluate its electrochemical performance.

[0051] Example 3

[0052] In the first step, the vacuum degree is 1×10 -5 Under the condition of pa, metallic cobalt with a purity of 99.98% is placed on a flat graphite plate and heated to 1350°C by laser to vaporize the metallic cobalt into gaseous cobalt nanoparticles to obtain cobalt vapor, which is then collected.

[0053] In the second step, cobalt vapor and carbon tetrafluoride gas are introduced into the reactor at a molar ratio of cobalt element to fluorine element of 1:2 and a gas flow rate of 20 ml / min. The reaction time is 2.5 hours to generate cobalt fluoride nanoparticles, which are in situ deposited on the surface of the graphene substrate to obtain a carbon composite cobalt fluoride positive electrode material, which is then collected after cooling.

[0054] The obtained carbon composite cobalt fluoride positive electrode material, conductive agent acetylene black and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, stirred until the viscosity reached the coating requirement, and then the mixture was evenly applied on aluminum foil using a coating machine. It was vacuum dried at 80°C for 12 hours.

[0055] After that, the dried electrode was cut into discs with a diameter of 12 mm. The loading amount of active material on each disc was about 2.5 mg / cm 2 .

[0056] The prepared electrode sheet was used as the positive electrode, the lithium sheet as the negative electrode, and Celgard 2500 as the separator. The entire process was completed in an argon-filled glove box to complete the assembly of the CR2032 button battery. The electrolyte of the assembled CR2032 button battery was 1 mol / L lithium hexafluorophosphate (LiPF 6 ), the solvent of the electrolyte is ethylene carbonate (EC) and dimethyl carbonate (DMC), wherein the volume ratio of EC to DMC is 1:1.

[0057] After assembly, the button cell was left to stand for 8 hours. At room temperature, the charge, discharge and cycle tests were performed on a Blue Power Battery Test System (CT2001A) with a test voltage of 1.0-4.0V and a current density of 0.1C to evaluate its electrochemical performance.

[0058] Figure 2-7 The curve diagrams are obtained by performing the first week charge and discharge test and the cycle test on the button type batteries prepared in the above three embodiments at a current density of 0.1C.

[0059] like Figure 2 As shown in the figure, the first week charge capacity of the carbon composite iron fluoride positive electrode material prepared in Example 1 is 248.5 mAh / g, and the discharge capacity is 270.2 mAh / g. Figure 3 As shown, after 100 cycles, the discharge specific capacity is 261.0 mAh / g and the capacity retention rate is 96.6%.

[0060] like Figure 4 As shown in , the carbon composite copper fluoride positive electrode material prepared in Example 2 has a first-week charge capacity of 411.8 mAh / g and a discharge capacity of 562.3 mAh / g. Figure 5 As shown, after 50 cycles, the discharge specific capacity is 489.2 mAh / g and the capacity retention rate is 87.0%.

[0061] like Figure 6 As shown in the figure, the first week charge capacity of the carbon composite cobalt fluoride positive electrode material prepared in Example 3 is 443.5 mAh / g, and the discharge capacity is 455.2 mAh / g. Figure 7 As shown, after 50 cycles, the discharge specific capacity is 396.6 mAh / g and the capacity retention rate is 87.1%.

[0062] It can be seen that the preparation method proposed in the present invention can improve the conductivity of the material, realize rapid electron transmission and ion migration, reduce the internal stress of the electrode, alleviate volume expansion, and the prepared carbon composite transition metal fluoride material has a high initial capacity and a relatively stable cycle performance, without the adverse condition of rapid capacity decay. The problems of voltage hysteresis, low reversible capacity and rapid decay caused by poor conductivity and slow reaction kinetics of transition metal fluorides are improved.

[0063] Example 4

[0064] In the first step, the vacuum degree is 2×10 -4 Under the condition of pa, metallic nickel with a purity of 99.99% is placed in an electron beam evaporation device and heated to 1300°C by an electron beam to vaporize the metallic nickel into gaseous nickel nanoparticles to obtain nickel vapor, which is then collected.

[0065] In the second step, nickel vapor and nitrogen trifluoride gas are introduced into the reactor at a molar ratio of nickel to fluorine of 1:2.5 and a gas flow rate of 25 ml / min. The reaction time is 2 hours to generate nickel fluoride nanoparticles, which are in situ deposited on the surface of the biomass-derived carbon substrate to obtain a carbon-composite nickel fluoride positive electrode material, which is then collected after cooling.

[0066] Example 5

[0067] In the first step, the vacuum degree is 3×10 -5 Under the condition of pa, metallic zinc with a purity of 99.95% is placed in a microwave heater and heated to 300°C by microwaves to vaporize the metallic zinc into gaseous zinc nanoparticles to obtain zinc vapor, which is then collected.

[0068] In the second step, zinc vapor and carbon tetrafluoride gas are introduced into the reactor at a molar ratio of zinc to fluorine of 1:2 and an air flow rate of 10 ml / min. The reaction time is 6 hours to generate zinc fluoride nanoparticles, which are in situ deposited on the surface of the carbon paper substrate to obtain a carbon composite zinc fluoride positive electrode material, which is then collected after cooling.

[0069] Example 6

[0070] In the first step, the vacuum degree is 1×10 -4 Under the condition of pa, metallic titanium with a purity of 99.9% is placed in a microwave heater and heated to 1400°C by microwaves to vaporize the metallic titanium into gaseous titanium nanoparticles to obtain titanium vapor, which is then collected.

[0071] In the second step, titanium vapor and carbon tetrafluoride gas are introduced into the reactor at a molar ratio of titanium to fluorine of 1:4 and a gas flow rate of 20 ml / min. The reaction time is 3 hours to generate titanium fluoride nanoparticles, which are then in situ deposited on the surface of a metal organic framework (MOF) / polymer-derived porous carbon substrate to obtain a carbon-composite titanium fluoride positive electrode material, which is then collected after cooling.

[0072] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a carbon composite transition metal fluoride positive electrode material, characterized in that: The preparation method comprises: Under vacuum conditions, heat-treating a transition metal element so that the transition metal element is vaporized into gaseous metal nanoparticles to obtain transition metal vapor; The transition metal vapor and the fluorine source gas are introduced into a reaction container containing a porous carbon substrate, and the transition metal vapor and the fluorine source gas undergo a gas phase reaction to generate transition metal fluoride nanoparticles, which are in situ deposited on the surface of the porous carbon substrate to obtain a carbon composite transition metal fluoride positive electrode material.

2. The preparation method according to claim 1, characterized in that: The vacuum condition is specifically: the vacuum degree is less than 10 - 3 pa; the heat treatment temperature is 300°C-3000°C, and the different transition metal elements correspond to different heat treatment temperatures.

3. The preparation method according to claim 1, characterized in that: The heat treatment includes any one of resistance heating, high frequency induction heating, laser heating, electron beam heating, microwave heating or arc heating.

4. The preparation method according to claim 1, characterized in that: The gas flow rates of the transition metal vapor and the fluorine source gas are both 10 ml / min to 30 ml / min; and the reaction time of the gas phase reaction is 0.5 hour to 6 hours.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the metal element in the transition metal vapor to the fluorine element in the fluorine source gas is 1:1-1:

6.

6. The preparation method according to claim 1, characterized in that: The transition metal single substance includes any one of the metal elements Fe, Co, Mn, Ni, Cu, Zn, Nb or Ti; the purity of the transition metal single substance is greater than 99.8%.

7. The preparation method according to claim 1, characterized in that: The fluorine source gas is nitrogen trifluoride or carbon tetrafluoride.

8. A carbon composite transition metal fluoride positive electrode material, characterized in that: The carbon composite transition metal fluoride positive electrode material is prepared by the preparation method described in any one of claims 1 to 7 above.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the carbon composite transition metal fluoride positive electrode material according to claim 8.

10. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • System and method for preparation of metal fluoride-coated lithium-ion battery anode material based on chemical vapor deposition method of fluidized bed

    CN109666918A

  • Ferric fluoride / carbon composite positive electrode material, preparation method thereof and lithium ion battery

    CN113241443A

  • Preparation method for synthesizing iron trifluoride carbon positive electrode material by using gas phase fluorination

    CN114447318A

  • Secondary battery functional material as well as preparation method and application thereof

    CN116014143A

  • Metal fluoride coated lithium intercalation material and methods of making same and uses thereof

    US20180233770A1